Case Report: CD19 and CD20 monoclonal antibodies with sequential chemotherapy for refractory acute B-lymphocytic leukemia in children - Li, Jia-Nan; Li, Yu; Lin, Ji-Xun; Wang, Li-Na; Zhang, Xiao-Li; Ouyang, Juan; Chen, Du-Bo; Chen, Shao-Qian; Li, Jun-Xun; Luo, Xue-Qun; Tang, Yan-Lai; Huang, Li-Bin (Frontiers in Immunology, 2023)
Objective: This paper observes the efficacy of chemotherapy combined with CD19 and CD20 monoclonal antibodies in clearing minimal residual disease (MRD) and bridging transplantation for refractory acute B-lymphoblastic leukemia (B-ALL) in children and reviews the literature. Methods: A 4-year-old boy diagnosed with B-ALL in our hospital was treated with the SCCLG-ALL-2016 protocol. MRD and gene quantification decreased after induction but remained persistently positive, with poor efficacy. After this patient received three cycles of consolidation chemotherapy combined with blinatumomab and rituximab, MRD and fusion gene quantification became negative, and he received allogeneic hematopoietic stem cell transplantation (allo-HSCT).Results: During the use of monoclonal antibodies, neurotoxicity, CRS, or other side effects did not occur. Before transplantation, MRD became negative, and the bone marrow had been in complete remission since transplantation (13 months).Conclusions: Chemotherapy combined with blinatumomab for refractory B-ALL in children can bring a better remission rate for patients and is a means of bridging transplantation.Nevertheless, sequential CD20 monoclonal antibody therapy is the first report, and no adverse effects were observed in our case. It is well tolerated and can be used as one of the treatments for refractory B-ALL.